2021
DOI: 10.1177/1524838020985542
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Bonding Perspectives From Service Providers and Survivors of Sex Trafficking: A Scoping Review

Abstract: A trauma bond is an emotional attachment between an abuser and victim. Trauma bonds in sex trafficking compel victims to submit to continued exploitation and protect the trafficker. This scoping review examines trauma bonds in sex trafficking situations, its conceptualizations, and key characteristics. Ten databases were searched using sex trafficking AND trauma bonding–related terms; sex trafficking AND Stockholm syndrome, attachment, coercion, and manipulation. Articles were included if they featured trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…The relationship between mental disorders and human trafficking has been frequently discussed in past studies (Levine, 2017;Ravi et al, 2017;Casassa et al, 2021;Chambers et al, 2022). Three mental disorders which have been proposed by many researchers are: post-Trafficking Trauma: the psychological effects of human trafficking.…”
Section: Psychological Patternsmentioning
confidence: 99%
“…The relationship between mental disorders and human trafficking has been frequently discussed in past studies (Levine, 2017;Ravi et al, 2017;Casassa et al, 2021;Chambers et al, 2022). Three mental disorders which have been proposed by many researchers are: post-Trafficking Trauma: the psychological effects of human trafficking.…”
Section: Psychological Patternsmentioning
confidence: 99%
“…In addition to a general consensus surrounding the definition of trauma bonding, Casassa et al (2021) also identified four key aspects of trauma bonding that emerged from the literature: (1) a strong association between susceptibility to trauma bonding and prior abusive and exploitative experiences, specifically in childhood; (2) survivors' conviction of their love for their trafficker, which often persists even after exiting their trafficking situation; (3) feelings of affection motivate survivors to protect traffickers from legal consequences; and (4) traffickers' intentional exploitation of emotional vulnerabilities and basic attachment needs (i.e., love, safety, affection) in order to develop a traumatic bond. The paradoxical nature of trauma bonds has significant implications for survivors of sex trafficking (Casassa et al, 2021): (1) attachment to the perpetrator prevents survivors from leaving abusive situations (Baldwin et al, 2015;Reid et al, 2013); (2) attachments motivate survivors to protect perpetrators from legal consequences (Clawson et al, 2008;Nichols, 2016); and (3) survivors grow distrustful of outside or institutional systems that can offer help or protection (i.e., social services and police) as they internalize the perpetrator's perceptions of such systems as well as a sense of guilt (Sanchez et al, 2019), making survivors unlikely to utilize such services even when presented with the opportunity to do so. Thus, the development of trauma bonds themselves perpetuates physical, emotional, and mental exploitation.…”
Section: Trauma Bondingmentioning
confidence: 99%
“…Deleterious effects of complex trauma in conjunction with traffickers’ exploitative methods can produce trauma bonds that are extremely difficult to resolve (Reid et al, 2013). Trauma bonds refer to maladaptive emotional attachments that develop between victims and abusers across a variety of exploitive relationships (Casassa et al, 2021; Hopper, 2017a; Reid et al, 2013). Such attachments are fostered through cycles of abuse in which aversive arousal is alternated with relief, stimulating an intense attachment towards the abuser that is difficult to resolve (Dutton & Painter, 1993).…”
Section: Trauma Bondingmentioning
confidence: 99%
See 2 more Smart Citations